Bacteriology of moderate (chronic) periodontitis in mature adult humans. - Moore, W E (1983)
A total of 171 taxa was represented among 1,900 bacterial isolates from 60 samples of sites affected with moderate periodontitis in 22 mature adult humans. The composition of the subgingival sulcus flora was statistically significantly different from that of the adjacent supragingival flora and the subgingival flora of 14 people with healthy gingiva, but was not significantly different from that of sulci affected with severe periodontitis in 21 young human adults. The sulcus floras of moderate periodontitis and severe periodontitis shared many of their predominant bacterial species, but there were differences in the relative proportions of some of these species. Similar relationships were found for seven taxa of treponemes that were cultured from the samples.